pH-dependent protein stability switch coupled to the perturbed pKa of a single ionizable residue - Mishra, Prajna; Patni, Divya; Jha, Santosh Kumar (Biophysical Chemistry, 2021)
The contribution of electrostatic interactions in protein stability has not been fully understood. Burial of an ionizable amino acid inside the hydrophobic protein core can affect its ionization equilibrium and shift its pKa differentially in the native (N) and unfolded (U) states of a protein and this coupling between the folding/ unfolding cycle and the ionization equilibria of the ionizable residue can substantially influence the protein stability. Here, we studied the coupling of the folding/unfolding cycle with the ionization of a buried ionizable residue in a multi-domain protein, Human Serum Albumin (HSA) using fluorescence spectroscopy. A pHdependent change in the stability of HSA was observed in the near native pH range (pH 6.0-9.0). The protonation-deprotonation equilibrium of a single thiol residue that is buried in the protein structure was identified to give rise to the pH-dependent protein stability. We quantified the pKa of the thiol residue in the N and the U states. The mean pKa of the thiol in the N state was upshifted by 0.5 units to 8.7 due to the burial of the thiol in the protein structure. Surprisingly, the mean pKa of the thiol in the U state was observed to be downshifted by 1.3 units to 6.9. These results indicate that some charged residues are spatially proximal to the thiol group in the U state. Our results suggest that, in addition to the N state, electrostatic interactions in the U state are important determinants of protein stability.
Keywords: electrostatic interactions; Fluorescence spectroscopy; Thermodynamic stability; Unfolded proteins